A gestão patrimonial de bens móveis de caráter permanente na UFPB e na UFRN. - Nascimento, Stefanie Giulyane Vilela do (2013)
This paper aims to analyze the process of patrimony management of permanent movables in two public universities: UFPB and UFRN. The specific objectives are to carry out a diagnosis about the patrimony management of permanent movables on UFPB and to investigate the possible improvements that could be achieved by using the SIPAC, from experience of UFRN. For that, it describes the current public management, rescuing ideas that guide the behavior of these institutions in the management of public resources and identify legal, doctrinal and regulatory requirements to patrimony management in public agencies and on the institutions studied. Advocates the importance of information technology in the provision of public services and addresses the use of information systems as an important tool to support the performance of various organizational activities. Provides information about the SIPAC and others SIG developed by UFRN, characterizing it as potentially effective tool in helping management activities of chattels. This research is qualitative and quantitative and utilizes as a method of data analysis The Content Analysis. The data were collected from interviews and questionnaires answered by officers of UFPB as well as from interviews with UFRN servers. As auxiliary work tool was used the application NVivo 10 from QSR International. It concludes that both the general goal and the specific objectives were achieved. It is possible to have a vision of how has been worked the process of patrimony management of movables permanent in UFPB just like it is possible the understanding of how the patrimony management of chattels has been worked in UFRN from the use of SIPAC. This allows the perception of what this tool, if successfully implemented, would offer to the services of patrimony management on UFPB. At the end of this paper have some proposals to improvement in the management activities of chattels on UFPB.